Fuzzy multilayer perceptron with cuckoo search - Suwannee Phitakwinai (2018)
© 2018 Pushpa Publishing House, Allahabad, India. In this paper, we propose a fuzzy multilayer perceptron with cuckoo search for fuzzy vectors. We implement this algorithm on two real-world data sets, i.e., knowledge-based evaluator data set and postoperative patient data set. We also compare the results from the fuzzy multilayer perceptron with cuckoo search with that from the regular multilayer perceptron with cuckoo search of centroid of each fuzzy attribute and numeric value mapped from each fuzzy attribute. The fuzzy multilayer perceptron with cuckoo search provides a comparable result with those on the regular multilayer perceptron with cuckoo search on real number without any defuzzification.